Perancangan Bangunan Interior Sekolah Menengah Atas Kolese Santo Yusup Malang - Alex Triono; Andereas Pandu Setiawan; Poppy Firtatwentyna Nilasari (Intra, 2018)
School is a place where every individual had social interaction with each other. Therefore, schools need facilities to help students and teachers in maximizing their activities, both indoors and outdoors. Schools with poor circulation and air quality will not be able to accommodate learning activities in the room to run smoothly. According to Tunjung Atmadi, methodology is a means to solve a design problem which determines the success of an interior design. By understanding the design methodology, a design problem can be simplified into a clear and systematic classification. Moreover, providing a lot of openings and the use of cross ventilation system in the room results to an optimal interior daylighting and a good air quality to help improve school activities. A consideration in the placement of appropriate lighting and air circulation is needed in order not to disturb the learning process, especially the right circulation flow so that one does not disturb activities of the others.